Respuesta :

Answer:

         9    50

         10   69

Step-by-step explanation:

M^2 = M*M

       =  2 5       *       2 5

            1 8                1 8

      = (2*2) + (5*1)      (2*5) + (5*8) ..rows of the 1st matrix * column of 2nd matrix

         (1*2) + (8*1)       (1*5) + (8*8)

      =  4+5      10+40

          2+8      5+64

      = 9    50

         10   69

I am sorry i cannot solve the 2 one but i could solve the 1st one

Hope this helps

Answer:

        9    50

        10   69

Step-by-step explanation:

M^2 = M*M

      =  2 5       *       2 5

           1 8                1 8

     = (2*2) + (5*1)      (2*5) + (5*8) ..rows of the 1st matrix * column of 2nd matrix

        (1*2) + (8*1)       (1*5) + (8*8)

     =  4+5      10+40

         2+8      5+64

     = 9    50

        10   69